Caminhos e descaminhos da meritocracia contra as políticas de ação afirmativa na Universidade de São Paulo - Rodrigues, Josefa Neves (2016)
The present Master’s research has as its objective to analyze the policies of affirmative actions in the University of São Paulo on the assumption of meritocracy. This debate has been arousing polemics and raising matters regarding the importance of racial quotas implementation in this institution, claimed by social movements, specifically by the Black Awareness Center (NCN) and the Black Occupation. The affirmative action policies in Brazilian higher education have become a reality and have as an objective to fight against historical discrimination committed against black people, as well as constituting themselves as an instrument of social justice. Concerning Human Rights, racial inequality is seen as a violation of equality and difference. The affirmative actions, designated to the black population, are justified not only for the immensurable historical losses, but also, above all, for educational and political losses.